An Investigation of the Dynamic Response of Airway Smooth Muscle in Sensitized Animal Models - Jo-Avila, Miguel (Auckland University of Technology, 2014)
Asthma is a chronic respiratory disease, characterized by inflammation, airway hyperresponsiveness (AHR) and obstruction of the airways. During an asthma attack, the contraction of airway smooth muscle (ASM) in combination with increased mucus production reduces the bronchial diameter, increasing the resistance to airflow into the lungs. New Zealand has one of the highest prevalence rates for asthma in the world, with a total estimated cost around NZ$ 825 million per year. The intrinsic causes of asthma are currently not well understood. Several treatments have been developed, but none of them present a cure for this chronic disease. Most of these treatments pharmacological with side effects sometimes fatal and affecting many patients. Some patients show no response to existing treatments. ASM contraction is believed to be the main driving mechanism in asthma attacks. The response of ASM in healthy and asthmatic airways seems to be influenced by breathing patterns such as tidal breathing and deep inspiration, with strong differences between healthy and asthmatic airways. Therefore understanding airway mechanics and the dynamic response of ASM in vivo seems to be an essential component in the search for a new alternative in the treatment of asthma. The proposed research investigates the response of ASM in sensitized models in the presence of imposed oscillations in vivo and in vitro. The results from this study in combination with the previous work done in this area will help to increase the understanding of how length oscillations affect the response of ASM in healthy and asthmatic subjects.
Keywords: Airway smooth muscle; Length oscillations